PENGARUH LIQUID SUCTION HEAT EXCHANGER TERHADAP KINERJA SISTEM PENDINGIN PADA MESIN PORTABLE CHILLER - Sulistiono, Fajar Budi; Trisno, Ramon (Jurnal Rekayasa Mesin, 2023)
When the Covid-19 pandemic occured, most of the industries and public facilities were not used properly, but the cooling machines was still used, resulting in large consumption of power and electrical energy. Along with high energy consumption where the availability of energy is running low, savings are needed. As an alternative so that the cooling machine can save energy is to use the subcooling method, namely the addition of a liquid suction heat exchanger on a spiral portable chiller with 29 spirals. Furthermore, the refrigerant used in the portable chiller is R407c. This study aims to determine the effect and effectiveness of Liquid Suction Heat Exchanger on a portable chiller. The results obtained are the coefficient of performance on the non-Liquid Suction Heat Exchanger portable chiller is 4,699 with a cooling capacity of 6,668 kW and compressor performance of 1,419 kW while the portable chiller with the addition of Liquid Suction Heat Exchanger, the Coefficient Of Performance obtained is 5,197 with a cooling capacity of 6,719 kW and compressor performance of 1,219 kW. From the calculation above, the use of a liquid suction heat exchanger in a portable chiller can increase the cooling capacity by 1,97 %.